Are You “Gazing” at Me? How Others' Gaze Direction and Facial Expression Influence Gaze Perception and Postural Control - Lebert, Angélique; Chaby, Laurence; Guillin, Amandine; Chekroun, Samuel; Vergilino-Perez, Dorine (Frontiers in Psychology, 2021)
In everyday life, interactions between humans are generally modulated by the value attributed to the situation, which partly relies on the partner’s behavior. A pleasant or cooperating partner may trigger an approach behavior in the observer, while an unpleasant or threatening partner may trigger an avoidance behavior. In this context, the correct interpretation of other’s intentions is crucial to achieve satisfying social interactions. Social cues such as gaze direction and facial expression are both fundamental and interrelated. Typically, whenever gaze direction and facial expression of others communicate the same intention, it enhances both the interlocutor’s gaze direction and the perception of facial expressions (i.e., shared signal hypothesis). For instance, an angry face with a direct gaze is perceived as more intense since it represents a threat to the observer. In this study, we propose to examine how the combination of others’ gaze direction (direct or deviated) and emotional facial expressions (i.e, happiness, fear, anger, sadness, disgust and neutrality) influence the observer’s gaze perception and postural control. Gaze perception was indexed by the cone of direct gaze (CoDG) referring to the width over which an observer feels someone’s gaze is directed at them. A wider CoDG indicates that the observer perceived the face as looking at them over a wider range of gaze directions. Conversely, a narrower CoDG indicates a decrease in the range of gaze directions perceived as direct. Postural control was examined through the center of pressure displacements reflecting postural stability and approach–avoidance tendencies. We also investigated how both gaze perception and postural control may vary according to participants’ personality traits and emotional states (e.g., openness, anxiety, etc). Our results confirmed that gaze perception is influenced by emotional faces: a wider CoDGs was observed with angry and disgusted faces while a narrower CoDG was observed for fearful faces. Furthermore, facial expressions combined with gaze direction influence participants’ postural stability but not approach-avoidance behaviors. Results are discussed in the light of the approach-avoidance model, by considering how some personality traits modulate the relation between emotion and posture.